Co-delivery of pro-apoptotic biomolecules and drugs via amphiphilic block copolymer nanoparticles. - Tan, Mavis Shiuk Hui. (2009)
The therapeutic potential of anticancer chemotherapeutic agents has been restricted by dose-limiting toxicity and the occurrence of drug resistance in cancer cells which can develop over time. This study aims to utilize nanoparticle micelles which are self-assembled from the copolymer poly-{(N-methyldietheneamine sebacate)-co-[(cholesteryl oxocarbonylamido ethyl) methyl bis(ethylene)ammonium bromide] sebacate} (P(MDS-co-CES)) to encapsulate the anticancer drug doxorubicin. These drug-loaded micelles were used to form complexes with the anti-apoptotic protein tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) for co-delivery into cancer cells. Doxorubicin and TRAIL were able to synergistically enhance apoptosis in breast cancer cell line MDA-MB-231, but not in the caspase-8 deficient neuroblastoma cell line SH-SY5Y. The drug-loaded nanoparticle/TRAIL complexes were efficiently taken into cancer cells and localized mainly to the cell cytoplasm. Doxorubicin-loaded P(MDS-co-CES) micelle/TRAIL complexes demonstrated enhanced doxorubicin release in acidic pH (5.6) as compared to neutral pH (7.4). These complexes potentially provide selective drug release at specific acidic environments including the tumor microenvironment and in intracellular vesicles such as endosomes and lysosomes. The use of P(MDS-co-CES) to form nanoparticle micelle carriers is thus potentially able to co-deliver encapsulated drugs and pro-apoptotic biomolecules in complex with increased efficacy and greater specificity, and can reduce non-selective drug toxicity.